To the 100th anniversary of Professor Yuri Yuliyovych Kollontai — memory of the teacher (1925–2025) - Staff of "Orthopaedics, traumatology; prosthetics" (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
May 8, 2025 marks the 100th anniversary of the birth of Yuri Yuliyovych Kollontai, an orthopedic traumatologist, an outstanding scientist, and the founder of the Ukrainian school of hand surgery and tendon alloplasty.